ANALISIS PENDAPATAN USAHATANI SEMANGKA MITRA DAN NON MITRA DI KECAMATAN TUMIJAJAR KABUPATEN TULANG BAWANG BARAT - Annida Ubaidillah; Fembriarti Erry Prasmatiwi; Maya Riantini (Lampung University, 2020)
The objectives of this study are to know the implementation of watermelon farming on partnership and to compare the income of partner and non-partner watermelon farming in West Tulang Bawang Regency. The location of this study is chosen purposively in Tumijajar Subdistrict Tulang Bawang Barat Regency. The number of respondents is 65 farmers selected using census method. The data of this research were collected in January-April 2019. The partnership program is analyzed using descriptive qualitative and comparison of income of watermelon farmers on partnership and non-partnership is analyzed using income analysis. The results showed that the implementation of partnerships that are applied in watermelon farming in CV Salim Abadi is able to achieve production targets, plant care, group dynamics, discipline and discuss thesustainability of partnership programs. The average income obtained by partner watermelon farmers in Tumijajar Subdistrict is greater than non-partner watermelon farmers.Key words: income, partner, watermelon